Broadband spatio-temporal propagation characteristics of Airy plasmons - Singh, Amit; Falkner, Matthias; Steinert, Michael; Kaiser, Thomas; Isic, Goran; Pertsch, Thomas (OSA Continuum, 2020)
We experimentally investigate the propagation of Airy surface plasmon polaritons (Airy SPPs) on a gold film by multiphoton Photoemission Electron Microscopy (PEEM) at different excitation wavelengths and compare the result with rigorous numerical simulations. The typical bent trajectories of the excited two-dimensional beams are observed and analyzed over a wide range of wavelengths. We furthermore investigate the generation bandwidth of the diffraction grating from modal overlap calculations and evaluate the possibility of creating ultrashort Airy plasmon pulses. This provides a viable route to engineer two-dimensional ultrashort non-diffracting pulsed beams in the field of ultrafast nanophotonics.
CRIS-Team Scopus Importer:2023-04-20